Direct and indirect exciton transitions in two-dimensional lead halide perovskite semiconductors - Do, Thi Thu Ha (2021)
Atomically thin layers of two-dimensional lead halide perovskite semiconductors exhibit prominent light emission due to the inherently strong quantum and dielectric confinement. Electronic band structures and coupled electron-hole pairs (excitons), which govern the optical properties, are not well understood in these emergent two-dimensional materials. Here, we have performed both the steady-state and time-resolved photoluminescence spectroscopies with varying temperature to study the optical responses of a high-quality (PEA)2PbI4 single crystal. We observe a multitude of exciton transitions with different responses to temperature that suggests their different origins. Furthermore, our results suggest that the photoluminescence of layered perovskites is dominated by direct exciton transitions at low temperatures, while by an indirect exciton at high temperatures that can be explained by our proposed exciton band structure incorporating the interplay of Coulomb and Rashba effects. Our study sheds light on the intrinsic optical properties of two-dimensional perovskites that may be beneficial for the novel applications of perovskite-based devices.